2010
DOI: 10.1111/j.1757-1707.2010.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence characteristics, seed composition, and allometric relationships predicting seed yields in the biomass crop Cynara cardunculus

Abstract: Cynara (Cynara cardunculus) is a perennial C 3 herb that has its potential as bioenergy crop. This paper aims (a) to derive empirical relationships to predict cynara seed yield per head and per unit area, avoiding laborious extraction of seeds from the complex structure of its inflorescences; (b) to determine the head-weight distribution per unit area, the seed composition and the oil profile of cynara seeds; and (c) to estimate the range of cynara biomass, seed and oil yield in representative parts of Greece.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…Archontoulis et al. (2010) also found that the contents of oleic acid and linoleic acid accounted for 81.91% of the total fatty acids contents in the cardoon ( Cynara cardunculus L.).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Archontoulis et al. (2010) also found that the contents of oleic acid and linoleic acid accounted for 81.91% of the total fatty acids contents in the cardoon ( Cynara cardunculus L.).…”
Section: Discussionmentioning
confidence: 96%
“…The results of Zhang et al (2016) on Korean pine (Pinus koreansis) showed that oleic acid (C18:1) and linoleic acid (C18:2) were the most abundant fatty acids. Archontoulis et al (2010) also found that the contents of oleic acid and linoleic acid accounted for 81.91% of the total fatty acids contents in the cardoon (Cynara cardunculus L.).…”
Section: Oil Content and Fatty Acid Analysismentioning
confidence: 89%
“…However, as previously mentioned, the three oleaginous crops compared here show different seed yield and straw production. Although an overall range of 80-250 g· m −2 potential of seed yield is reported for cardoon [64], the average grain yield of 0.75 t· ha −1 and 10 t· ha −1 for straw considered in this paper is in accordance with the recent findings of [65]. In fact, those authors reported a mean seed yield of 603 kg· ha −1 in a large scale cultivation (77 ha) of the cardoon in southern Portugal and confirmed that this species is suitable for biomass production in Mediterranean regions.…”
Section: Oleaginous Crop Cultivationmentioning
confidence: 99%
“…[3.1]). For application examples, see Vega et al (2000), Vega and Sadras (2003), and Archontoulis et al (2010). The Michaelis-Menten equation (Eq.…”
Section: Group Vi-othersmentioning
confidence: 99%